2007
DOI: 10.1111/j.1743-7563.2006.00083.x
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter phase II study of combination chemotherapy with capecitabine and intravenous vinorelbine in patients with pretreated metastatic breast cancer

Abstract: Background: Capecitabine and i.v. vinorelbine are both active in metastatic breast cancer with nonoverlapping toxicities. This study examined the efficacy and safety of the combination of these agents in patients with pretreated metastatic breast cancer. Methods: Patients previously treated for breast cancer, maximum of one prior metastatic regimen, received capecitabine 1000 mg/m 2 b.d. for days 1-14 and vinorelbine 25 mg/m 2 i.v. days 1 and 8 every 21 days. All patients had measurable disease and adequate ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 31 publications
0
6
1
Order By: Relevance
“…In our study the response rate was 57% which is higher than that reported in some other trials, in which capecitabine-vinorelbine combination was used in pretreated MBC patients, and ranged from 33% to 50% 14,17,18 .…”
Section: Discussioncontrasting
confidence: 72%
See 1 more Smart Citation
“…In our study the response rate was 57% which is higher than that reported in some other trials, in which capecitabine-vinorelbine combination was used in pretreated MBC patients, and ranged from 33% to 50% 14,17,18 .…”
Section: Discussioncontrasting
confidence: 72%
“…On the other hand, the PFS in the present study (4.2 months) was lower than that reported in other studies. In studies that assessed the efficacy of capecitabine-vinorelbine combination as a second line in MBC, the time to progression ranged from 5.3 to 6 months 14,17,18 .…”
Section: Discussionmentioning
confidence: 99%
“…In other phase II trials [25][26][27][28][29][30][31] , the treatment was also safe and well tolerated. The most common severe hematologic toxicity was G3/4 neutropenia, probably a result of vinorelbine administration (6.6%-68.2%).…”
Section: Discussionmentioning
confidence: 95%
“…In other phase II trials in which the combination of capecitabine and vinorelbine was administered to patients with breast cancer pretreated with anthracyclines and taxanes Table (4) [25][26][27][28][29][30][31] , the RRs obtained ranged between 33% and 70%. In these studies, the median time to progression (TTP) ranged from 4.5 months to 10 months and the median OS was within 10 months and 30.4 months.…”
Section: Discussionmentioning
confidence: 99%
“…For all phase II combination studies (including trastuzumab combination in HER2-neu positive setting), the overall tumour RRs ranged from 33 to 75%, median OS from 13 to 35.8 months, median response duration from 2.6 to 17.5 months, median TTP (reported in two studies) from 6.6 to 8.6 months and median PFS (reported in two studies) from 9.6 to 9.9 months. The most commonly reported adverse events attributed to VI were neutropoenia, nausea, vomiting and alopecia [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28].…”
Section: Therapeutic Options After Anthracycline and Taxane-based Ctmentioning
confidence: 99%